Provisional versus elective two-stent strategy for unprotected true left main bifurcation lesions: Insights from a FAILS-2 sub-study. (1st January 2018) - Kawamoto, Hiroyoshi; Chieffo, Alaide; D'Ascenzo, Fabrizio; Jabbour, Richard J.; Naganuma, Toru; Cerrato, Enrico; Ugo, Fabrizio; Pavani, Marco; Varbella, Ferdinando; Boccuzzi, Giacomo; Pennone, Mauro; Garbo, Roberto; et al.
Abstract: Background: This study sought to investigate the optimal percutaneous coronary intervention (PCI) strategy for true unprotected left main coronary artery (ULMCA) bifurcations. Methods: The FAILS-2 was a retrospective multi-center study including patients with ULMCA disease treated with second-generation drug-eluting stents. Of these, we compared clinical outcomes of a provisional strategy (PS; n = 216) versus an elective two-stent strategy (E2S; n = 161) for true ULMCA bifurcations. The primary endpoint was the incidence of major adverse cardiac events (MACEs) at 3-years. We further performed propensity-score adjustment for clinical outcomes. Results: There were no significant differences between the groups in terms of patient and lesion characteristics. 9.7% of patients in the PS group crossed over to a provisional two-stent strategy. MACEs were not significantly different between groups (MACE at 3-year; PS 28.1% vs. E2S 28.9%, adjusted p = 0.99). The rates of target lesion revascularization (TLR) on the circumflex artery (LCX) were numerically high in the E2S group (LCX-TLR at 3-years; PS 11.8% vs. E2S 16.6%, adjusted p = 0.51). Conclusions: E2S was associated with a comparable MACE rate to PS for true ULMCA bifurcations. The rates of LCX-TLR tended to be higher in the E2S group although there was no statistical significance. Condensed abstract: This study sought to compare the clinical outcomes of a provisional strategy (PS) with an elective two-stent strategy (E2S) for the treatment of true unprotected left main coronary artery bifurcations. 377 Patients (PS 216 vs. E2S 161 patients) were evaluated, and 9.7% in the PS group crossed over to a two-stent strategy. E2S was associated with a similar major adverse cardiac event rate at 3-years when compared to the PS strategy (PS 28.1% vs. E2S 28.9%, p = 0.99). However, the left circumflex artery TLR rate at 3-year tended to be higher in the E2S group (PS 11.8% vs. E2S 16.6%, p = 0.51).